2020
DOI: 10.1017/s1368980020000944
|View full text |Cite
|
Sign up to set email alerts
|

TAG–glucose (TyG) index in childhood: an estimate of cut-off points and the relation to cardiometabolic risk in 4- to 9-year-old children

Abstract: Objective: To propose cut-off points for the TAG–glucose (TyG) index in Brazilian children and evaluate the link to cardiometabolic risk. Design: A cross-sectional study with children from a municipality in Minas Gerais, Brazil. Anthropometric (weight, height, waist circumference and waist:height ratio), biochemical (lipid and glucose profile) and blood pressure (BP) tests were performed. Using the receiver operating characteristic curve, cut-off points for the TyG index were proposed ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…IR is widely known as a primary risk factor for T2DM and CVD, and associated with metabolic abnormalities ( 7 , 8 , 26 ). On account of the complex detection process and the clinical complexity, the hyperinsulinemic euglycemic glucose clamp (HEGC), which was considered as the gold standard for IR assessment ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…IR is widely known as a primary risk factor for T2DM and CVD, and associated with metabolic abnormalities ( 7 , 8 , 26 ). On account of the complex detection process and the clinical complexity, the hyperinsulinemic euglycemic glucose clamp (HEGC), which was considered as the gold standard for IR assessment ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…The existing robust epidemiological evidence implies that insulin resistance (IR), which has been recognized as an independent risk factor, contributes to the initiation and perpetuation of CMDs ( 7 , 8 ). Nevertheless, the TyG-index, known as an alternative method for measuring IR ( 9 11 ), could be applied for clinical purposes and has shown a significant relation with IR ( 12 , 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…The TyG index is significantly associated with the presence of T2DM, nonalcoholic fatty liver disease (NAFLD), and MetS in adults and is a better predictor of IR than HOMA-IR 14 18 . Recent studies have reported that the TyG index can predict the presence and progression of coronary artery calcification (CAC) in adults and is associated with cardiovascular risk factors in children and adolescents 19 22 . Cutoff points for the TyG index for MetS and cardiometabolic risk have been suggested in many studies of children and adolescents, and the usefulness of screening has been sufficiently emphasized 22 25 .…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have reported that the TyG index can predict the presence and progression of coronary artery calcification (CAC) in adults and is associated with cardiovascular risk factors in children and adolescents 19 22 . Cutoff points for the TyG index for MetS and cardiometabolic risk have been suggested in many studies of children and adolescents, and the usefulness of screening has been sufficiently emphasized 22 25 . For the TyG index to be useful in clinical practice, it is necessary to determine its association with various confounding factors and whether it is consistently distributed in children and adolescents; however, studies on these characteristics are still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…The TyG index is signi cantly associated with the presence of T2DM, nonalcoholic fatty liver disease (NAFLD), and MetS in adults and is a better predictor of IR than HOMA-IR [14][15][16][17][18] . Recent studies have reported that the TyG index can predict the presence and progression of coronary artery calci cation (CAC) in adults and is associated with cardiovascular risk factors in children and adolescents [19][20][21][22] . In many studies in children and adolescents, cutoff points for the TyG index for MetS and cardiometabolic risk have been suggested, and its usefulness has been su ciently emphasized.…”
Section: Introductionmentioning
confidence: 99%